Improving cutoff frequency estimation via optimized π-pulse sequence - Zheng, Wang-Sheng; Zhang, Chen-Xia; Gong, Bei-Li (Chinese physics B, 2025)
The cutoff frequency is one of the crucial parameters that characterize the environment. In this paper, we estimate the cutoff frequency of the Ohmic spectral density by applying the π -pulse sequences (both equidistant and optimized) to a quantum probe coupled to a bosonic environment. To demonstrate the precision of cutoff frequency estimation, we theoretically derive the quantum Fisher information (QFI) and quantum signal-to-noise ratio (QSNR) across sub-Ohmic, Ohmic, and super-Ohmic environments, and investigate their behaviors through numerical examples. The results indicate that, compared to the equidistant π -pulse sequence, the optimized π -pulse sequence significantly shortens the time to reach maximum QFI while enhancing the precision of cutoff frequency estimation, particularly in deep sub-Ohmic and deep super-Ohmic environments.